KETERAMPILAN KARYAWAN DAN KINERJA OPERASIONAL PADA USAHA KULINER: KETAHANAN INTERNAL SEBAGAI VARIABEL MEDIASI - Fausya, Riza; Sutrino, Sutrino; Yulianti , Rika; Ismail , Junaldi; Zaitul, Zaitul (Gapenas Publisher, 2025)
This study aims to examine the influence of employee skills on operational performance in Minang culinary micro, small, and medium enterprises (MSMEs) in Padang City, with internal resilience serving as a mediating variable. A quantitative approach was applied, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both the measurement and structural models. A total of 49 respondents were selected through simple random sampling. The findings reveal that employee skills significantly affect internal resilience but do not directly impact operational performance. Conversely, internal resilience has a significant influence on operational performance and mediates the relationship between employee skills and business outcomes. These results highlight the importance of strengthening internal organizational systems to ensure that individual competencies translate into improved performance. The practical implication of this study suggests the need for integrated human resource development strategies aligned with internal resilience to support the sustainability of local MSMEs.